Squamous Cell Papilloma of the Urinary Bladder Endoscopically Mimicking Cancer - Dimosthenis Miliaras; Ioannis Vakalopoulos; Eleftherios Anagnostou (Case Reports in Pathology)
Squamous cell lesions of the urinary bladder are generally rare. Herein we describe a case of 74-year-old male patient with a benign squamous cell papilloma. Histologically, the tumor presented extensive keratinization at its surface and showed no nuclear atypia or stromal invasion. The tumor cells were negative for HPV DNA. These lesions are extremely rare, and even though they are considered benign and non-HPV related, they should be followed, since recurrence has been reported.